International experience in using artificial intelligence in accounting, auditing and reporting of enterprises. - HOLOVASH, Bohdan; HOLOVASH, Liliia; HICHAK, Bohdan (Ways to Improve Construction Efficiency, 2025)
The article examines the international experience of using artificial intelligence technologies in accounting, financial reporting, and auditing of enterprises. It is substantiated that under conditions of intensive digitalization of the economy, the functional role of accounting is being transformed—from a traditional tool for recording business transactions into an intelligent system for data analysis, forecasting, and decision support. It is determined that modern artificial intelligence technologies create new opportunities for the automation of accounting processes, as well as for improving their accuracy and efficiency. The paper provides an overview of the global market for the use of artificial intelligence in accounting, auditing, and reporting. It is established that this market is characterized by high growth rates driven by the development of generative AI, the implementation of cloud technologies, and the digitalization of financial processes. Key market segments are analyzed by components, deployment models, enterprise size, and application areas. Special attention is paid to the analysis of the advantages of using artificial intelligence in accounting practice. It is found that the implementation of AI ensures the automation of routine operations, reduces the number of errors, increases the reliability of accounting information, and improves internal control and audit systems. It is determined that the use of intelligent systems enables in-depth analysis of financial data in real time, timely identification of risks, fraudulent activities, and anomalies, as well as the formation of well-grounded managerial decisions. In addition, the use of AI contributes to cost optimization, increased labor productivity, and the development of employees’ analytical competencies. At the same time, the article outlines the main challenges and limitations of AI implementation, including the technical complexity of integration, the need for significant investments, regulatory uncertainty, cybersecurity risks, and the necessity to adapt human resources to new conditions. The importance of developing an appropriate regulatory framework, advancing digital infrastructure, and improving the level of digital literacy among professionals is emphasized. It is concluded that the integration of artificial intelligence technologies into accounting, financial reporting, and auditing is a key direction for the modernization of modern enterprises and an important factor in enhancing their competitiveness in the global market. The feasibility of adapting leading international practices to the conditions of the Ukrainian economy, taking into account its institutional and structural features, is substantiated.